Implications of Tumor Size on Auditory Brainstem Implant Performance - Cottrell, Justin; Breen, Matthew; Leeuwen, Matthew V.; Shapiro, William; Azadpour, Mahan; Friedmann, David; Jethanamest, Daniel; McMenomey, Sean; Pacione, Donato; Hagiwara, Mari; Moonis, Gul; Golfinos, John; Roland, J. Thomas, Jr. (Journal of Neurological Surgery Part B: Skull Base, 2025)
To better understand the implications of tumor size on auditory brainstem implant (ABI) categories of auditory performance (CAP) score to facilitate more precise patient counselling.Single-center retrospective chart review.Tertiary referral center.Patients > 18 years old with neurofibromatosis type 2 who underwent ABI placement between the years 2009 and 2023 were included. Patients with prior surgical resection were excluded to reduce the potential of previous cochlear nucleus trauma confounding results.Ipsilateral tumor volume was measured from the preoperative MRI, and the primary endpoint was the 1-year CAP score.Fourteen patients were included for analysis, with an average age of 35.3 years. The average preoperative ipsilateral tumor volume was 22.8 cm3 (± 22.4). The average postoperative CAP score was 2.7 (± 2). A negative association was found between ipsilateral tumor size prior to treatment and CAP score (slope = − 0.058, p = 0.010) utilizing a linear regression model. The model accounted for 43.7% of the variance in outcome (R2 = 0.437, adjusted R2 = 0.390), with a significant overall model fit (F [1, 12] = 9.31, p = 0.010).Increased tumor size has a negative correlation with ultimate ABI performance. There were patients in this study with larger tumor sizes who still benefited from ABI placement. While larger tumor size should not be a contraindication for ABI placement, understanding the role tumor size can have on performance variation can serve to improve tumor management strategies and preoperative counselling.
Keywords: ABI performance; vestibular Schwannoma; NF2; CPA tumor; auditory brainstem implant